A infância é um direito? - Sarmento, Manuel Jacinto; Tomás, Catarina (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2020)
In current language “childhood” is a word with a normative connotation expressed. Childhood is a kind of moral quality, associated with the age of children but which surpasses it, covered with characteristics such as naivety, natural kindness, creativity, dreamy spirit, the playful meaning of life, the “natural beauty of things”. This conception, however, drags with it an exclusive sense, expressed in words like “children who never had childhood”, and it can even drag with it the idea of “bad childhood” by subversion some moral attributes. In this article we discuss the concept of childhood, changing it as a generational, universal and permanent social category, although marked by social inequality and diversity, through interception with other social categories, namely class, gender and ethnicity. Thinking about childhood from a critical sociological perspective, implies the deconstruction of the normative conception of childhood and the focus on social factors that, simultaneously, contribute to the justification of the universality of children's rights and the analysis of the inequality of its application.